2006
DOI: 10.1111/j.1442-2042.2006.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s gangrene: Report of thirty‐three cases and a review of the literature

Abstract: Background: Fournier's gangrene (FG) is an extensive fulminant infection of the genitals, perineum or the abdominal wall. The aim of this study is to share our experience with the management of this difficult infectious disease. Methods: Thirty-three male patients were admitted to our clinic with the diagnosis of FG between February 1988 and December 2003. The patient's age, etiology and predisposing factors, microbiological findings, duration of hospital stay, treatment, and outcome were analyzed. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 36 publications
5
95
1
12
Order By: Relevance
“…Tissue destruction then results from a combination of ischemia and the synergistic action of various bacteria. 8,18 In our study, the mean extent of the body surface area involved in the necrotizing process was lower in patients who survived than that in those who died but, we did not find a significant difference (p = 0.067).The studies by Laor et al and Clayton et al suggested that the extent of disease was not predictive of outcome. However, in a study by Spirnak et al a greater extent of the disease was associated with a greater mortality rate for patients who had more frequent operations.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Tissue destruction then results from a combination of ischemia and the synergistic action of various bacteria. 8,18 In our study, the mean extent of the body surface area involved in the necrotizing process was lower in patients who survived than that in those who died but, we did not find a significant difference (p = 0.067).The studies by Laor et al and Clayton et al suggested that the extent of disease was not predictive of outcome. However, in a study by Spirnak et al a greater extent of the disease was associated with a greater mortality rate for patients who had more frequent operations.…”
Section: Discussioncontrasting
confidence: 49%
“…Bacteroides, and clostridia are also frequently identified. 8,19 Paty and Smith 20 reported E. coli, Bacteroides and streptococci to be the most common organisms in FG. Laor et al 11 determined the most common organisms to be E. coli and Streptococcus species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] The previous reports suggested the highest incidence of male patients in the 6th decade of life. [29][30][31][32][33] Even with the lower incidence rates, the disease was found in females and in all age groups of childhood including newborn and infancy periods. [33][34][35][36][37][38][39][40] The results of the present report were in agreement with the literature regarding age and sex.…”
Section: Ciprofloxacin 40mentioning
confidence: 99%
“…The very large body of clinical evidence for the effectiveness of honey in heaHng wounds has been reviewed [127 1 , The evidence covered in that review, plus that from trials published since the review was published [128][129][130][131][132][133][134], is from 23 randomized controlled trials involving a total of 2257 participants, seven clinical trials of other forms involving 142 participants treated with honey, four case studies where there were multiple wounds allowing comparison of honey with other treatment and 16 trials of honey on a total of 533 wounds in animal models (which rule out a placebo effect). Mostly the wounds involved were infected.…”
Section: Clinical Evidence For Effectiveness Of Honey On Infected Woundsmentioning
confidence: 99%